1107 Arousal And Sleepiness In Opioid Use Disorder Compared To Insomnia Disorder With And Without Comorbid Psychiatric Conditions - Krishnamurthy, V B; Hussain, N; Puzino, K; Yadav, S; Del Tredici, S; Vgontzas, A N; Bixler, E O; Fernandez-Mendoza, J (Sleep (New York, N.Y.), 2020)
Abstract Introduction Insomnia is frequent in opioid use disorder patients on buprenorphine (OUDB) and increases risk of relapse. There is lack of data evaluating specific differences in hyperarousal and daytime sequelae between OUDBs as compared to individuals with insomnia disorder without (ID) or with comorbid psychiatric conditions (CID). Methods We studied 112 patients with ID (47.8±16.3y, 55% female, 13% minority) and 148 with CID (44.7±15.6y, 69% female, 16% minority) evaluated at the Behavioral Sleep Medicine program of Penn State Hershey Sleep Research & Treatment Center and 71 OUDB (37.8±11.2y, 51% female, 16% minority) evaluated at the Recovery, Advocacy, Empowerment and Service program and WellSpan Internal Medicine clinics (York, PA). Subjects completed the Insomnia Severity Index (ISI), Ford Insomnia Response to Stress (FIRST), Arousal Predisposition Scale (APS), Pre-sleep Arousal cognitive (PSAS-C) and somatic (PSAS-S) Scale, Dysfunctional Beliefs and Attitudes about Sleep Scale (DBAS) and Epworth Sleepiness Scale (ESS). Excessive daytime sleepiness (EDS) was defined as an ESS score ≥ 10. MANCOVA included age, sex, race/ethnicity and depression as covariates, while logistic regression further included ISI, APS and PSAS-S. Results No differences across groups were observed in PSAS-C or DBAS scores. Subjects with CID and OUDB had significantly higher PSAS-S (15.7±0.5 and 16.4±0.7, respectively) and APS (35.6±0.6 and 36±1, respectively) scores as compared to the ID group (14.2±0.6 and 33.2±0.7, respectively). Subjects with OUDB had significantly higher ESS score (9.8±0.6) as compared to the ID or CID groups (6.2±0.5 and 6.4±0.4, respectively). The odds of EDS were 2.7 times (95%CI=1.2-6.1) higher in the OUDB group as compared to the ID group. Conclusion OUDB may present with similar phenotypic insomnia symptoms as patients with ID or CID but report more sleep-disturbing somatic symptoms and EDS. These data have important implications for tailoring behavioral and pharmacological treatments of insomnia to this specific patient population. Support Junior Faculty Development Program, Penn State College of Medicine